PEMANFAATAN RESIN KITOSAN-AMIN UNTUK RECOVERY EMAS DARI LIMBAH PENGOLAHAN EMAS - M. Nasir; Adlim Adlim; Ibnu Khaldun; M. Ali Zulfikar (Universitas Syiah Kuala, 2012)
Chitosan as a material of biological origin has recently been used for recovery of metal ions. This research aims to synthesize kitosan resin resulted by the reaction of kitosan with etilendamin. In the present work chitosan was cross-linked with glutardialdehyde and subsequently treated with epichlorohydrine and ethylene diamine. The resins CR-amine was found to contain 22.7% water content, and were insoluble in organic solvents as well as in mineral and organic acids. The concentration values of the active sites on the resins are reported. The higher concentration of active sites of CR-amine 6.01 mmol/g indicates that the “en” moieties are covalently bonded to the cross-linked resin. Several chemical modification methods were tried in increasing the uptake capacity of cross-linked chitosan bead. Among them, aminated chitosan beads formed through the chemical reaction using ethylenediamine showed the highest uptake capacity for gold ions. Uptake capacity of aminated chitosan beads was increased to about 0.8 mmol Au3+ g-1 dry mass compared to that before modification. The increase of amine groups was confirmed by IR spectrum and measurement of amine concentration and surface condition on aminated chitosan bead was also confirmed by SEM.